Efektivitas Penggunaan Media Pembelajaran Komedi Putar Membaca Dalam Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas 1 SD Negeri Krapyak Wetan - Adha, Idyana; Hariko, Rezky; Karneli, Yeni (Widyagogik, 2024)
Professional counseling is fundamentally based on a trusting relationship, upheld by strict ethical principles such as confidentiality. While maintaining client confidentiality is a non-negotiable cornerstone of practice, counselors require effective, ethical techniques to facilitate meaningful change. This article explores the integrated use of two such powerful techniques: interpretation and body awareness strategies. Interpretation allows the counselor to offer insights and connect patterns in the client's thoughts and behaviors, while body awareness techniques help clients access and process unconscious emotions and trauma stored somatically. When combined, these strategies provide a holistic framework that bridges cognitive understanding and embodied experience. This article argues that this integration can significantly deepen client self-understanding and promote more profound therapeutic outcomes. The discussion includes the theoretical underpinnings of this approach, practical methods for its implementation, and its applicability within both individual and group counseling settings, all while adhering to the highest ethical standards of the profession.